1977
DOI: 10.1007/bf01686316
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological analysis in a case of endosulfan suicide

Abstract: Stomach, small intestine contents, blood, liver, kidney and urine of a 28-years old man, were analyzed for residues of Endosulfan (6, 7, 8, 9, 10, 10-hexachloro-1, 5, 5a, 6, 9, 9a-hexahydro-6, 9-methano-2, 4, 3-benzo(e)dioxathiepin 3-oxide). The analysis results showed the presence of high concentrations of the two endosulfan isomers in all samples. Since also alcohol was present in all the tissues analyzed, it was concluded that the victim died of a combined endosulfan-alcohol poisoning. No other drugs were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…All were treated by gastric lavage and developed tonic-clonic convulsions 1±4 h post ingestion. In another fatal case the reported blood levels were 0.075 mg/L several hours after ingestion which was complicated by the presence of alcohol [Demeter et al, 1977] (see Table II for a comparison of endosulfan blood levels). Eighteen additional incidents of occupational endosulfan exposure associated with convulsions have been documented in recent literature [Chugh et al, 1998].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All were treated by gastric lavage and developed tonic-clonic convulsions 1±4 h post ingestion. In another fatal case the reported blood levels were 0.075 mg/L several hours after ingestion which was complicated by the presence of alcohol [Demeter et al, 1977] (see Table II for a comparison of endosulfan blood levels). Eighteen additional incidents of occupational endosulfan exposure associated with convulsions have been documented in recent literature [Chugh et al, 1998].…”
Section: Discussionmentioning
confidence: 98%
“…In one case, a man consumed endosulfan and dimethoate in xylene and alcohol. In another report, authors concluded that a fatality was due to synergistic effects of alcohol and endosulfan [Demeter et al, 1977].…”
Section: Chemical Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Endosulfan acts as an antagonist to the inhibitory neurotransmitter Gama-aminobutyric acid (GABA) by inactivating GABA A-dependent chloride channels. Several cases of suicidal and accidental poisoning, as well as chronic poisoning, with endosulfan have been reported in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Poisoning with endosulfan produces strong sulfur odors, and the clinical picture is comprised of three stages: the acute cardiac and convulsive stage, followed by the sub-acute pulmonary and convulsive stage, and finally, the slow recovery stage (2).…”
Section: Discussionmentioning
confidence: 96%
“…Its full name is 6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro-6,9-methano-2,4,3-benzo(e) dioxathiepin 3-oxide, and it is used as a pesticide (1). It is absorbed from the gastrointestinal tract, respiratory system, and skin.…”
Section: Discussionmentioning
confidence: 99%